Effects of Magnetically Treated Water on Male Sexual Traits in Broiler Breeder During Hot Climate in Summer - Mahbuba GH. Mustafa (Mesopotamia Journal of Agriculture)
This experiment was conducted at the Poultry private farm in Taqtaq - Erbil to determine the effect of magnetically treated water on male sexual traits in broiler breeder during hot climate in summer. A total of 80 Cobb-500 cocks, 40 weeks old were allocated randomly into four treatment groups with four replicates. Magnetically treated water were served in cocks drinking from the first day of experiment until the end which lasted 4 months (June, July, August and September). Experimental treatments were as follows: Treatment T1: control group (well water), Treatments T2, T3 and T4 used magnetically treated water with strength 500, 1000 and 2000 gauss in drinking water. Results indicated significant increase in: semen volume, spermatozoa concentration , mass motility, individual motility and spermatocrit, but showed significant decrease in: percentages of dead, abnormal spermatozoa, acrosomal abnormalities, semen plasma traits were also evaluated in relation to concentrations of glucose, cholesterol, protein and activities of GOT and GPT enzymes in seminal plasma in magnetically treated water treatments T4 (2000 gauss) and T3 (1000 gauss) as compared with T2 (500 gauss) and T1 (control group) in most traits above. The cocks resulted significant improvement in reproductive performance of the cocks during September .